Characterization of grown-in defects in Si wafers by gas decoration. (1st August 2021) - Liu, Yun; Wei, Tao; Li, Minghao; Li, Zhan; Xue, Zhongying; Wei, Xing
Abstract: In this paper, a vapor gas etching method is developed to systematically characterize grown-in defects such as crystal originated particles (COPs), oxygen precipitates (OPs) and dislocations in 300 mm boron-doped (001) Czochralski (CZ) silicon wafers. For a given type of defect, an unique morphology reveals after selective etching by hydrogen chloride (HCl) at 1000 °C. The etching mechanism is discussed and the characteristic morphology of bulk defects is investigated by localized light scattering (LLS), scanning electron microscopy (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM). Analyzing the data obtained by these techniques, it can be found that the defect types could be differentiated by light scattering signal, i.e., latex sphere equivalent (LSE) size, and defect regions could be divided by the etch pit density. Moreover, due to the effect of HCl etching, the OP as small as several nanometers can be measured directly by SEM and AFM. This study provides Si industry with a fast and comprehensive defect delineation method. Highlights: In this paper, HCl etching is used to characterize silicon crystal defects including void, oxygen precipitate and dislocation. Preferential etching of HCl leads to characteristic morphology that is unique to a given type of defect. A light scattering tool(SP5), widely used in semiconductor fabs, is used to differentiate the decorated defects. The etching mechanism is discussed and the source and nature of decorated defects are investigated by SEM, AFM and TEM. Moreover, grown-in defects with the scale of several nanometers exposed by HCl etching is capable to be measured directly